Qur'anic Recitations (Qira'at) in the Context of Tafsir al-Mazhari - Mr. Aziz Haider; Muhammad Hameed; Dr. Hafiz Mohsin Zia Qazi; Dr. Zaheer Ahmad; Mr. Muhib Ullah (Al-Qanṭara, 2022)
The Noble Qur'an was revealed to the pure heart of His Beloved Prophet Muhammad ﷺ so that humanity could be guided by it. It was revealed in different dialects and recitations, so that it was easy for people to recite and understand Yes, recitation is very important in Quranic sciences, especially in the subcontinent, Qazi Sanaullah explained the foundations of its understanding and jurisprudential issues very well in Tafsir-i-Mazhari and made the Quranic teachings public. We will discuss it in the light of Tafseer-e-Mazhari. Keywords: Qur'an, Revealed, Muhammad, Humanity, Important, Understanding, Jurisprudential, Discuss, Tafseer-e-Mazhari